THE CHARACTERISTIC OF SOILS WITH ANDIC PROPERTIES DERIVED FROM ACID PYROCLASTIC MATERIALS IN TOBA HIGH LAND - PRASETYO, BAMBANG HENDRO; SUHARTA, NATA; YATNO, EDI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
Soil with andic properties are generally found in Indonesian volcanic high land. To characterize the andic soils, six pedons derived from pyroclastic rock from Toba high land were studied. Properties of the andic soils from Toba high land were somewhat different from others andic soils in Indonesia. Results of chemical and mineralogical data interpretation showed that the andic soils from Toba were derived from acid pyroclastic rock. This indicate that andic soils in Indonesia not only derived fromintermediate to basic volcanic rock, but also from acid rock. The main problem of andic soils is in their high P retention. In the study area the P retention range between 34-95%, the soils are acid to very acid (pH 5.5-4.1), poor of nutrients, and some of them have very high Al saturation (>60%). Increasing exchangeable Al occur at pH 4 to 5, while the high Al saturation occur at concentration of exchangeable Al between 0.5 to 3cmolc kg-1. High value of P retention was caused by high content of amorphous materials, indicate by positive relationships between P retention and Al + ½Fe extracted by ammonium oxalate (R2 = 0,88). Clay mineral identification is needed to distinguis between amorphous and crystallin minerals that can be used as a basic of better soil management.